Renoprotective action of mucosa-adhesive phytogel "Biotrit" in rats, treated with oral application peroxide sunflower oil - Stepan, V. T. (Journal of Education, Health and Sport, 2020)
Aim. Determine the renoprotective activity of oral “Biotrit” gel when exposed to peroxide sunflower oil (PSO). Methods. PSO was obtained by heating the oil at +180 ° C for 60 minutes in the presence of 1.5% H2O2. Used mucosa-adhesive phytogel "Biotrit", containing bioflavonoids from wheat leaves. Rats received oral applications of PSO at a dose of 0.5 ml/rat for 5 days. A part of the rats received 30 minutes before the application of the PSO application of the “Biotrit” gel. The activity of elastase, catalase, urease, lysozyme and the content of MDA were determined in the kidneys. The ratio of catalase and MDA was calculated the API index, and the ratio of the relative activities of urease and lysozyme – the degree of dysbiosis. Results. In rats treated with PSO, the activity of elastase, urease, and MDA content increased but lysozyme activity and the API index decreased in the kidneys. Applications of the gel "Biotrit" reduce the activity of elastase, urease, increase the activity of lysozyme and the API index. Conclusion. Consumption of PSO causes the development of nephropathy; Oral applications of the gel "Biotrit" prevent the development of peroxide nephropathy.